2019
DOI: 10.1063/1.5121546
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the subgrid-scale gradient model for compressible magnetohydrodynamics turbulent instabilities

Abstract: Performing accurate large eddy simulations in compressible, turbulent magnetohydrodynamics is more challenging than in non-magnetized fluids due to the complex interplay between kinetic, magnetic and internal energy at different scales. Here we extend the sub-grid-scale gradient model, so far used in the momentum and induction equations, to account also for the unresolved scales in the energy evolution equation of a compressible ideal MHD fluid with a generic equation of state. We assess the model by consideri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(74 citation statements)
references
References 91 publications
8
65
0
Order By: Relevance
“…times. This behavior on the magnetic energy spectra of LES was also found in our bounding-box simulations [43][44][45].…”
Section: B Less With Gradient Sgs Modelsupporting
confidence: 85%
See 2 more Smart Citations
“…times. This behavior on the magnetic energy spectra of LES was also found in our bounding-box simulations [43][44][45].…”
Section: B Less With Gradient Sgs Modelsupporting
confidence: 85%
“…However, finite-difference numerical methods are usually more dissipative (and dispersive). Therefore, as shown in [43][44][45], the value that best mimics the feedback of small scales onto the large scales in a LES can differ depending partially on the numerical methods employed and on the specific problem. In practice, one needs a calibration of the different SGS parameters to maximize the effectiveness of the gradient model.…”
Section: Large Eddy Simulations In Grmhdmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way that numerical relativity simulations of BBH mergers have been critical for the detection and characterization of these sources with GW observations, numerical relativity simulations of BNS and NSBH mergers are critical to get insights into the physical processes that may lead to the production of electromagnetic and astro-particle counterparts, and to better interpret MMA observations 67 . These modeling efforts do not currently benefit from DL, but recent studies have suggested the possibility to improve the efficiency and robustness of simulations, enabling the inclusion of detailed microphysics [68][69][70][71][72] , and a significance increase in the speed with which partial different equations are solved 73,74 .…”
Section: Real-time Detection Of Gws and Neutrinosmentioning
confidence: 99%
“…In what we will call "large-eddy simulations," it is assumed that a significant portion of the inertial range is resolved, and subgrid stress terms are computed as an extrapolation of the character of resolved turbulence to subgrid scales (e.g., [18][19][20][21]). An example of such methods is the gradient model that has recently been adapted to relativistic magnetohydrodynamics by Carrasco, Viganò, and Palenzuela [22] (see also [23]). The subgrid dynamo term of Giacomazzo et al [4] might also fit into this category, because the field growth is stopped when the magnetic energy density approaches an estimate of the subgrid turbulent kinetic energy density.…”
Section: Introductionmentioning
confidence: 99%